Answer:
W=4h(11-j)/b-h
Step-by-step explanation:
Eliminate variables on the left side first.
b(h+w) = 4h (11-j) - so, divide b by both sides
(h+w)/b=4h(11-j)/b then, eliminate h by subtracting on both sides.
(h+w)-h=4h(11-j)/b - h (h is eliminated on the left side and now you are left with
W=4h(11-j)/b - h
An expression that is equivalent to the statement Subtract a from the quotient of 6 and B is 6/b - a
Given statement
Subtract a from the quotient of 6 and B
6/B - a
Therefore, the correct option equivalent to the statement is option A) 6/B - a
Learn more about equivalent expression:
brainly.com/question/2972832
43/8
if you split 5 into parts of 8 than that becomes 40/8 plus the 3/8 is 43/8
2^2 ( 1,2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12) = 4, 8, 12, 16, 20, 24, 28, 32, 36, 40, 44,48
3^2(1,2,3, 5) = 9, 18, 27, 45
5^2(1, 2) = 25, 50
7^2 = 49
19 numbers